KESIAPAN SANTRI DALAM MENGIKUTI ANALISIS NASIONAL PKPPS ANWARUL HASANIYYAH (ANWAHA)KABUPATEN TABALONG - Syahrani Syahrani (CV. ADIBA ASIHA AMIRA, 2025)
The results showed that the students in participating in national analysis at PKPPS Anwarul Hasaniyyah (Anwaha), Tabalong Regency belonged to the category of quite ready. This is supported by: the mental and physical readiness of the students to take the computer based national exam at PKPPS Anwarul Hasaniyyah (Anwaha), Tabalong Regency, the unskilled students in operating computers, and the students mastery of the subject matter included in the AN, especially materials that have been completed discussed at school.